2007
DOI: 10.1680/geot.2007.57.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structure on the time-dependent behaviour of a stiff sedimentary clay

Abstract: In this paper results from laboratory tests on London Clay and artificially cemented kaolin are presented and used to develop a preliminary framework for the timedependent behaviour of soils, applicable to stiff clays and other soils. In the same way that the natural structure of clays has been shown to influence their monotonic behaviour, it is shown that it can also alter their response to changes in strain rate. The relative influence of the two main components of post-sedimentation structure-overconsolidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 17 publications
4
29
0
2
Order By: Relevance
“…The effects of structure on the soil mechanical behaviour in shearing and compression for natural London clay have been studied in detail at Imperial College, London (Gasparre et al 2007b;Gasparre et al 2007a;Hight et al 2007;Gasparre 2005) and University College, London (Sørensen et al 2007). During the tests a large effect of particular the post-sedimentation structure was found.…”
Section: Influence Of Structure On Deformation Behaviour Of Claysmentioning
confidence: 99%
“…The effects of structure on the soil mechanical behaviour in shearing and compression for natural London clay have been studied in detail at Imperial College, London (Gasparre et al 2007b;Gasparre et al 2007a;Hight et al 2007;Gasparre 2005) and University College, London (Sørensen et al 2007). During the tests a large effect of particular the post-sedimentation structure was found.…”
Section: Influence Of Structure On Deformation Behaviour Of Claysmentioning
confidence: 99%
“…The values of , m and reference strain rate were taken from the simulation of the work done by Sorensen et al (2007), while the string lengths were fitted to stiffness degradation data obtained by Gasparre (2005), Figure 7. The fit deviates in the very small strain region to take account of the elastic shear modulus, G max , measured using bender elements.…”
Section: The Influence Of Recent Stress History and Creep On Stiffnessmentioning
confidence: 99%
“…Recent testing conducted on London Clay has shown that, not only is the small strain behaviour inelastic and non-linear, but it is also susceptible to the effects of creep and other viscous phenomena (Gasparre et al, 2007;Sorensen et al, 2007). Indeed, the need to take account of creep when conducting triaxial stress path tests is well recognised (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilation can cause suction at some conditions of drainage and dilation rate. At critical and residual states (no dilation) the strength of soil remains rather unaffected by the rate of shearing under low to medium strain rate (Sorensen, Baudet & Simpson, 2007;Diaz-Rodriguez, Martinez-Vasquez & Santamarina, 2009;Bhat, Bhandary & Yatabe, 2013). The effect of strain rate on effective strength parameters remains unclear.…”
Section: Introductionmentioning
confidence: 99%